Dealing with unclaimed dead bodies- embrace the challenge - Pankaj, Arora; Singh, Bhogal Ranjitpal (International Journal Of Community Medicine And Public Health, 2017)
Background: Worldwide a significant number of unclaimed dead bodies report to hospital and health authorities find it difficult to clear them from morgues. The epidemiology of these unclaimed dead bodies and various methods to identify them has been studied by various forensic experts but no study has considered pitfalls in dignified disposal of the dead bodies. Methods: As a part of routine set up of mortuary, a designated person among the staff of mortuary has been assigned the task of keeping the record of unidentified dead bodies and facilitating their disposal with the help of local police and police under whose jurisdiction the case falls. The same data has been collected retrospectively between the period from 1st April 2014 to 31st March 2015. Results: In this study our designated person, in coordination with local police, was able to expedite the process of disposing these dead bodies on an average in 9.7 days; in accordance with the law and as per the customary rituals, where ever possible. This reflects an extraordinary work beyond the routine tasks given to this indispensable and highly motivated worker. Conclusions: However, this points to a possible need for development of a mechanism, where it is not dependent on individual efforts.